Use of and willingness to pay for Climate Information Services (CIS) in Senegal - Muriithi, Cyrus; Ouedraogo, Issa; Siagbe, Golli; Diouf, Latyr; Maina, Wilson (2024)
Senegal faces significant challenges related to food insecurity, affecting 16% of its population due to low crop yields, rapid population growth, and reliance on cereal imports for 60% of its needs. Climate change has intensified droughts, floods, and coastal erosion, disrupting key sectors like agriculture, livestock, fisheries, and tourism. Rainfall has declined by 15% since the 1950s, while temperatures have risen 0.9°C annually since 1975, with further increases expected by 2035. These changes exacerbate land degradation, causing soil salinity, erosion, and waterlogging, especially in flat landscapes with poor drainage. Limited irrigation (only 33% of potential) further hinders agricultural productivity. The crop sector relies on rain-fed production of millet, peanuts, maize, and rice, while livestock farming (cattle, goats, sheep, chickens) remains a key income source. To combat these challenges, Senegal must strengthen climate information services and promote climate-smart agricultural practices to improve decision-making, reduce risks, and enhance the resilience of farming systems.